Birds of wetlands in Peninsular Malaysia - Hussin, Mohamed Zakaria; Rajpar, Muhammad Nawaz (Universiti Putra Malaysia Press, 2014)
This book would provide a brief introduction about wetland areas, their importance and threats. In addition, the book envisages the morphology behavior, habitat preference and foraging behavior of waterbirds as well as terrestrial birds that may utilize the wetland habitats in search of food and shelter. This book is divided into three sections; the first section elaborates the morphology and ecology of waterbird species in different wetland habitats. Finally the third section describes the morphology and ecology of terrestrial bird species that also utilizes wetland areas in search for food and shelter.